Java message service - Richards, Mark (W. Mark) (O'Reilly, 2009)
Java Message Service, Second Edition, is a thorough introduction to the standard API that supports ""messaging""--The software-to-software exchange of crucial data among network computers. You'll learn how JMS can help you solve many architectural challenges, such as integrating dissimilar systems and applications, increasing scalability, eliminating system bottlenecks, supporting concurrent processing, and promoting flexibility and agility. Updated for JMS 1.1, this second edition also explains how this vendor-agnostic specification will help you write messaging-ba